Dinamika Sosial Perkembangan Pemerintahan Gemeente Mojokerto Tahun 1918-1942 - Firmanda Dwi Septiawan (LP4MK STKIP PGRI Lubuklinggau, 2022)
Mojokerto is a city of the former Majapahit kingdom which is famous for ruling the archipelago to foreign countries. During the Mataram kingdom, Mojokerto was still called Japan and was included in the area of ​​the Regent of Overseas Wetan. Over time and the arrival of colonial residents in Mojokerto has changed the shape of the city. The construction of infrastructure by the European people did not make this city develop well. Very unlike other colonial cities such as Surabaya, Malang, Madiun which developed and developed into a developed city. Mojokerto has only become a small town, and is very much against the hopes and stories of previous triumphs. This paper aims to describe several things, including the development process in Mojokerto City until it was determined to be a gemeente (1918-1942), and the impact of the origin of the formation of gemeente on the development of the Mojokerto community in 1918-1942. Although the development was actually intended for the people of Europe, the people of Bumi Putra also felt the positive impact of this development. The developments carried out are the construction of markets, government buildings, road and village repairs, public baths and the provision of hygienic water.